Captivating moments at the INFORMS grand meeting / Dr. Hajah Imilia Ibrahim and Ainaa Insyirah Saliman - Ibrahim, Imilia; Saliman, Ainaa Insyirah (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
The Information Management Society (INFORMS) semester grand meeting at UiTM Sarawak was organized on October 13, 2023. The meeting was conducted at the UiTM Samarahan Campus's Dewan Kuliah 1. Generally, the meeting is a recurring event scheduled for the first or second week of each semester during lecture weeks. It was held during the first week of this semester. The meeting holds significance as it provides a forum for lecturers, faculty members, and members of the society to exchange current and critical information regarding the academic and extracurricular pursuits of the faculty. In addition, the purpose of the meeting was to provide an introduction of the new students to the entire faculty.